Perlakuan Air Panas pada Umbi Bawang Merah (Allium cepa var. ascalonicum) untuk Menekan Infeksi Virus di Lapangan - Harti, Heri; Sobir; Wiyono, Suryo; Hendrastuti Hidayat, Sri (Jurnal Hortikultura Indonesia, 2019)
High infestation of viruses on shallot’s bulb has been reported, although little is known on the effect of virus infection on shallot productivity. The use of virus-free bulbs is assumed to be the key factor to improve productivity. Hot water treatment of bulbs before planting is one of methodologies to eliminate virus from shallot bulbs. Therefore, research was conducted to study the effectiveness of hot water treatment methods of shallots bulbs to reduce virus infections in the field. Field experiment was conducted using split plot randomized block design with two factors. The first factor was the use of netting, i.e. growing shallot in netting house and in open field. The second factor was hot water treatment of shallot bulb at 45 0C for 15, 30, and 45 min and without treatment. Observations were conducted on the incidence of virus infections, plant growth (number of tillers and plant height) and shallots productivity. Virus infection was confirmed using specific antibodies. Observation of disease symptom indicated that the use of netting house did not significantly suppress the incidence of virus diseases, while hot water treatment significantly reduced the incidence of virus diseases. Hot water treatment for 15, 30 and 45 minutes at 45 0C was able to suppress virus incidence in the field up to 54.98%, 56.77% and 64.35%, respectively.Key words: netting house, soaking time, viruses elimination, virus incidence